Berbeda Dalil dan Berbeda Ritual: Analisis Pemahaman Hadis tentang Doa dalam Khutbah di Kalangan Nahdlatul Ulama dan Muhammadiyah - Maulana, Arif; Damanik, Nurliana (Sekolah Tinggi Agama Islam Sumatera Medan, 2023)
Two major Islamic mass organizations in Indonesia kece slot which often differ in religious practices, often trigger gaps by pointing fingers at each other for right and wrong. In this regard, this study aims to analyze the differences in praying in Friday sermons among Nahdlatul Ulama and Muhammadiyah. The focus of research on the kece slot differences in the implementation of Friday sermons and hadiths about prayer in Friday sermons. The research method is a qualitative type with a case study approach with a focus on differences in prayers in Friday sermons between Nahdlatul and Muhammadiyah. Sources of research data are Nahdlatul Ulama and Muhammadiyah Deli Serdang officials. Data collection by observation, interviews and documentation. Data analysis with stages of data grouping, data interpretation and data presentation. The research findings explain that Nahdlatul Ulama and Muhammadiyah differ in the implementation of Friday kece slot prayers, such as the number of call to prayer, the technique of praying, the attitude of the congregation in praying. The hadiths used as arguments, namely Nahdlatul Ulama refer to authentic hadiths narrated by Muslim, Abu Daud, Tirmizi which show that one must raise one's hands when praying on the pulpit. Meanwhile, the hadith referred to by Muhammadiyah comes from authentic hadiths narrated by Muslim, Tirmizi and al-Nasa'i which show that one must lift the index finger when praying on the pulpit. Differences in the source of hadith as an argument is the cause of differences in the practice of religious rituals.